2022
DOI: 10.3390/scipharm90030055
|View full text |Cite
|
Sign up to set email alerts
|

LC-HRMS-Based Profiling: Antibacterial and Lipase Inhibitory Activities of Some Medicinal Plants for the Remedy of Obesity

Abstract: Globally, obesity is a serious health concern that causes numerous diseases, including type 2 diabetes, hypertension, cardiovascular diseases, etc. Medicinal plants have been used to aid in weight loss since ancient times. Thus, this research is focused on the exploration of pancreatic lipase inhibitory activity and secondary metabolite profiling of Bergenia ciliata, Mimosa pudica, and Phyllanthus emblica, selected based on an ethnobotanical survey. The lipase inhibition was investigated using 4-nitrophenyl bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 80 publications
1
2
0
Order By: Relevance
“…At a low MG concentration, the growth inhibition by MG decreased in a dose-dependent manner, which might imply that MG could still help to reduce the pathogenicity of this yeast at low concentrations. In accord with the anti- M. globosa lipase activity by MG reported here, an anti-pancreatic lipase activity by MG was previously reported [ [75] , [76] , [77] ].…”
Section: Discussionsupporting
confidence: 92%
“…At a low MG concentration, the growth inhibition by MG decreased in a dose-dependent manner, which might imply that MG could still help to reduce the pathogenicity of this yeast at low concentrations. In accord with the anti- M. globosa lipase activity by MG reported here, an anti-pancreatic lipase activity by MG was previously reported [ [75] , [76] , [77] ].…”
Section: Discussionsupporting
confidence: 92%
“…Several studies demonstrated the presence of flavonoids in invasive M. pudica plant: Sapkota et al . reported that an ethyl-acetate fraction of M. pudica growing in Nepal contained quercetin, catechin, and avicularin [ 60 ]; Yusof et aldetermined orientin, kaempferol 7-rutinoside, and kaempferol 3-glucoside-7-rhamnoside in M. pudica aerial parts [ 61 ]; and Lobstein et al . isolated myricetin and two C-glycosylflavones, 4″-hydroxymaysin and cassiaoccidentalin B, from M. pudica aerial parts [ 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, anti-M. globosa lipase activity by MG has not been reported yet. It was previously reported that MG from methanolic extract of Galla Rhois (IC 50 > 300 𝜇M), and other natural extracts which containing MG including ethyl extract of Phyllanthus emblica (IC 50 2.45 ± 0.003 mg/ml), and aqueous extracts of Rhus coriaria (IC 50 19.95 𝜇g/ml) had inhibitory activity to pancreatic lipase (Jaradat et al, 2017;Kwon et al, 2013;Sapkota et al, 2022).…”
Section: Chapter V Discussionmentioning
confidence: 99%